1999
DOI: 10.1021/jp991443w
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond Photoluminescence Study of then-GaAs(100)/Methanol Interface in a Photoelectrochemical Cell

Abstract: Anodic photocorrosion and cathodic photowashing of n-GaAs(100) in a nonaqueous photoelectrochemical cell have been studied using photoluminescence decays and the voltage dependence of both photoluminescence intensity and photocurrent. Photocorrosion of the cell, which is attributed to trace water contamination, results in an increased surface recombination velocity and an overall loss in photoluminescence intensity, but does not affect the photocurrent. The stability of the photocurrent upon corrosion of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…In opposite, InP, presents an "unexpected" slope of 40 mV [3] if we consider the whole pH range. Two nernstian V fb behaviors were nevertheless observed for limited ranges of pH (0-4) and (8)(9)(10)(11)(12)(13)(14) while in the neutral pH range a non-nernstian variation was still detected. These behaviors revealed that a pure nernstian evolution depends essentially on the pH stability of the surface chemistry which supports the acid-base equilibrium [3].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In opposite, InP, presents an "unexpected" slope of 40 mV [3] if we consider the whole pH range. Two nernstian V fb behaviors were nevertheless observed for limited ranges of pH (0-4) and (8)(9)(10)(11)(12)(13)(14) while in the neutral pH range a non-nernstian variation was still detected. These behaviors revealed that a pure nernstian evolution depends essentially on the pH stability of the surface chemistry which supports the acid-base equilibrium [3].…”
Section: Introductionmentioning
confidence: 93%
“…According to the pH ranges, two different chemical compositions of InP surface were indeed determined by XPS chemical analyses. Either in acidic pH range (0-4) or basic pH range (8)(9)(10)(11)(12)(13)(14) a chemical composition close to a bare InP surface was determined, while a presence of a oxide mixture and hydroxide was analyzed only in neutral pH range [3]. How can we explain the nernstian potential variation observed onto a bare surface in aqueous media?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…water chemistry (e.g. Refs [7][8]). As a singular electrolyte, liquid ammonia (NH 3 liq) is distinguished from the other nonaqueous solvents since moisture does not interact at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Abshere et al [4,5] had clearly demonstrated the fact that the photocorrosion of GaAs is ruled by traces of water in anhydrous methanol.…”
Section: Introductionmentioning
confidence: 99%